La Interfaz Sintaxis-Pragmática Estudios teóricos, descriptivos y experimentales - Belloro, Valeria A. (De Gruyter, 2019)
Privileging functionalist approaches-based on descriptions of natural discourse and independent from formal grammatical models-, this collected volume gathers original contributions on the syntax-pragmatics interface in Spanish as well as in indigenous languages of the Americas, and explores related topics like topical continuity or Preferred Argument Structure.